The Influence of Peers, Parents, and Media on Ann’s Body Image in Kelly Barson’s 45 Pounds - Dewi, Riska; Marsih, Linusia (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
This thesis discusses body image in Kelly Barson’s novel 45 Pounds through the main character Ann, focusing on her mental image of her body and the factors influencing it. This qualitative research uses in-depth text analysis and a psychological approach, employing body image theories by Calogero & Thompson and factors influencing body image by Van Den Berg & Thompson et al. The analysis reveals that Ann has a negative body image, evident in her perception, attitude, and behavior towards her body. This negative image is influenced by peers, parents, and media. Negative comments, teasing, and behaviors from peers and parents, as well as media portrayals, contribute to Ann's body dissatisfaction. The study concludes that peers, parents, and media significantly impact Ann's negative body image. To build a positive body image, one must accept oneself, focus on health rather than size, and avoid comparisons. Peers, parents, and media should provide positive examples and encouragement regarding body and appearance.